“Pathetic ccholarship” in Gukurahundi and related studies : a silver lining from - Shai, Kgothatso B (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
“In every dark cloud, there is a silver lining”. In this context, the perceived prevalence of pathetic scholarship in Gukurahundi studies and other cognate fields is cause for concern among scholars and practitioners. However, pathetic scholarship is not uniformly understood by interested parties, who largely base their arguments on Euro-American perspectives that only provide a partial understanding of this phenomenon. Against this backdrop, this paper seeks to critique pathetic scholarship, whether real or imagined, in Gukurahundi Studies, Media, Politics, Conflict, and Peace Studies, just to mention a few. For this paper, pathetic scholarship is understood as studies of sub-standard in terms of set criteria. Methodologically, this paper employs conversations and interdisciplinary discourse analysis with an alternative Afrocentric approach. In this paper, it is argued that pathetic scholarship has not yet reached a crisis point. In fact, pathetic scholarship (in its current form) carries the hopes and aspirations for interdisciplinary richness in tackling difficult subjects such as Gukurahundi and apartheid.
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 7 (2) (2023)
Keywords: Facebook; Social media; Knowledge; Development; South Africa; Mass media -- Social aspects; Scholarships